Strategi Pengembangan Bisnis Rental Mobil Wiralodra 27 dengan Pendekatan Model Bisnis Kanvas - Andi Agustiadi; Rizal Syarief; Dodik Ridho Nurrochmat (Jurnal Aplikasi Bisnis dan Manajemen (JABM), 2018)
Wiralodra 27 rental car is a car service provider in Bogor city. Due to the high potential market in this industry, the car rental company requires an appropriate business model and new strategies in the face of competition. The objectives of this research are 1) to identify present business model of the company using the canvas business model approach; 2) to analyze each element that becomes the strength, weakness, opportunity and threat that affect the business model of the company; 3) formulate strategies to improve the canvas business model; and 4) to make recommendations for the improvement program of the business development of Wiralodra car rental 27. The method used in this research included the canvas business model and SWOT analysis as a tool of analysis. The respondents of this research consisted of 5 members of the Board of Director of the company and one senior employee. In addition, there were also twenty four customer respondents who were selected with purposive sampling. The research results showed recommendations for the improvements of all key elements of the canvas business model. The main priority scales of the improvements are the elements of customer segment, key partnership, revenue stream for associated risk factors of the business. The second priority scales of the improvements are the elements of value propositions, channel, customer relationship, key resources, key activities, and cost structure.Keywords: canvas business model, rental car services, SWOT, Wiralodra